Level of service acceptability matrix (LOSAM) for active mobility - Chee, Darilynn Rui Bin (Nanyang Technological University, 2021)
Traffic planning and design have been a serious challenge in Singapore due to land scarcity and traffic congestion, coupled with competing needs despite Singapore goal towards transforming into a car-lite society. Like several other cities, Singapore is remodelling and improving transportation systems to favour active mobility mode of transport (AMT) over automobiles by utilizing advancement in technology and creative ideas such as artificial intelligence. (URA, 2019) To reduce public reliance on automobile and head towards usage of public transport, car sharing service and AMT, the Land Transport Authority gathers the public’s opinions and concerns by collecting their feedback for the Land Transport Master Plan (LTMP) 2040. (Loo, Lai, & Kein, 2001) LTA has also made an announcement stating annual allowable car growth will be reduced to 0 in 2018. These factors have undoubtedly made AMT become increasingly popular thus increasing demand for non-motorised traffic (NMT), directly increasing the use of shared off-road facilities. Shared off-road facilities provides infrastructure for the use of different active mobility device users or active users, including pedestrian, cyclists, personal mobility device (PMD), power-assisted bicycles (PAB), personal mobility aid (PMA) users. (Koh, 2012) Hence, it is important to re-evaluate and adjust the road and facilities accordingly to ensure the safety and satisfaction of the users is met. However, with 12% of Singapore’s land already being taken up by roads (the same amount as housing) and the limited land resource that we currently have, it is crucial to allocate the resources optimally by considering the safety and comfortability when using the facility. (Phang & Toh, 2004) To address this issue, transportation engineers have calibrated and established a user-rated serviceability measures by considering the Level of Service (LOS) as a mechanism that measures the satisfaction of a consumer using the transportation facility. (Khisty, 1994) A low LOS level is a representative of the users feeling unsafe which is a good indication of how safe the transportation facility is operating. So far, there have been considerable number of studies and research conducted on the evaluation of the LOS in automobile roads and the LOS in non-motorised space for pedestrian and cyclist. Research studies have also been conducted to examine mixed non-motorised traffic behaviour and characteristics in a local environment. (Koh, 2015) However, there are limited data on the evaluation of the LOS in non-motorised shared space for other active mode of transport such as PMD, PMA, PAB. It is crucial to take active mobility devices (AMD) into consideration as the increase usage of AMD on active mobility facilities space can reduce the LOS of pedestrians greatly. Therefore, this FYP project aims to re-calibrate the Level of Service Availability Matrix (LOSAM) for various types of active mobility users in non-motorised shared space and study the impact of different type of active mobility facilities on LOSAM. The findings from this study provide valuable information for transport professionals in the planning, design and management of AMT infrastructure. This research study has also brought upon the development and application of new analysis techniques and models which would be valuable to academic researchers.